2011
DOI: 10.2166/wst.2011.580
|View full text |Cite
|
Sign up to set email alerts
|

Priority organic pollutants in the urban water cycle (Toulouse, France)

Abstract: Application of the European Water Framework Directive requires Member States to have better understanding of the quality of surface waters in order to improve knowledge of priority pollutants. Xenobiotics in urban receiving waters are an emerging concern. This study proposes a screening campaign of nine molecular species of xenobiotics in a separated sewer system. Five sites were investigated over one year in Toulouse (France) using quantitative monitoring. For each sample, polycyclic aromatic hydrocarbons, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Like organotins, this family of molecules, potentially used in certain automotive oils, is very poorly documented. To date, only one study has analyzed LAS in road runoff and pointed out much higher concentrations (43-590 µg/L) [28]. As expected, due to their physical-chemical properties, PAHs and PBDE are mainly detected in the particulate fractions (suspended solids or sediments) rather than the dissolved phase (Figure 2).…”
Section: Micropollutants In the Road And Parking Lot Runoff-prevalenc...mentioning
confidence: 73%
See 1 more Smart Citation
“…Like organotins, this family of molecules, potentially used in certain automotive oils, is very poorly documented. To date, only one study has analyzed LAS in road runoff and pointed out much higher concentrations (43-590 µg/L) [28]. As expected, due to their physical-chemical properties, PAHs and PBDE are mainly detected in the particulate fractions (suspended solids or sediments) rather than the dissolved phase (Figure 2).…”
Section: Micropollutants In the Road And Parking Lot Runoff-prevalenc...mentioning
confidence: 73%
“…The non-quantification of oxygenated ethers in the runoff, although they are potentially emitted following the combustion of fuels, could be linked to their very rapid volatilization due to their physical-chemical properties. Previously reported concentrations of MTBE ranged from 0.03 to 1.9 µg/L [26][27][28]. A recent study indicated that the concentrations of oxygenated ethers were below 0.03 µg/L [20].…”
Section: Micropollutants In the Road And Parking Lot Runoff-prevalenc...mentioning
confidence: 98%
“…There is high variability in detergent formulation. However, the active molecule most used in these cleaning products belongs to the group of alkylbenzene sulfonates [24,25].…”
Section: Detergentsmentioning
confidence: 99%
“…Depending on the species, the concentrations at which chronic effects are observed vary between 250 and 10,000 µg L −1 [46]. Additionally, these substances contribute to the permeation of other toxic compounds into aquatic animals [24]. Alkylbenzene sulfonates are mostly treated in wastewater treatment plants in an activated sludge process [47], and some of them are degraded by indigenous microorganisms when they reach the natural receiving environment.…”
Section: Alkylbenzenesmentioning
confidence: 99%
“…En effet, celle-ci joue un rôle dans la solubilité des gaz, dans la dissociation des sels dissous et dans la détermination du pH et les mélanges éventuels . D'une façon générale, la température des eaux est influencée par l'origine dont elles proviennent Breton et al, 2010;Sablayrolles et al, 2011 (Abdoulkadri et al, 2015).…”
Section: La Méthode Des Ajouts Dosésunclassified